The external debt situation of the least developed countries - Piritta Sorsa (Intereconomics, 1991)
While the external debt of the least developed countries (LLDCs) is no threat to the international financial system, its adverse impact on the development efforts of many of these countries is severe. The following article examines their debt and economic situation and reviews major elements of the current international debt strategy with regard to their adequacy in bringing the LLDCs back to sustainable debt burdens and growth.
Keywords: 330; Indebtedness